Faktor-Faktor yang Mempengaruhi Pembentukan Akhlak Dalam Kalangan Pelajar Sekolah Menengah Umum (SMU) di Kota Medan - Syarifah (2011)
This study aim to identify factors which influenced moral formation in students from four fruits secondary school announce (SMU) in town Medan. Between factors that can affect moral formation in students is religious education grant that sufficiently role of school in disciplining student, parents' role, role of mass media, and filling way free time that empty with things that beneficial free time that unfilled with as good as will cause student tend to use up diversion time good moral. This study carried out with early observation method that extended with form distribution method investigate to students in that four fruits school that is participated interview to teachers and Head master the school. Form investigate that used fall into various parts namely A part and B. The generally A part contain background information respondent and B part contain items related to study issue. Likert scale was invoked to make assessment at all item which include in B. part. Item interview that open to teachers and teachers candidate. Data study achieved than questionnaires and interview that was being conducted that in schools. Study findings show that formation capacity moral in SMU Town Medan's students was very good, until happened increase and moral rehabilitation by slow. This state bring about crime total reduction which is done by SMU student in town Medan. This Study Impact on Solution of Factors which Influenced moral Formation in Sekolah Menengah Umum's Students in Town Medan will prevent youth depravity. This case important extended continuously nonstop as early action prevention to prevent do maksiat and crime in general in town Medan.